Fired up! Ready to Go! Finding Beauty, Demanding Equity: An African American Life in Art. - Cooper Cafritz, Peggy; Akunyili Crosby, Njideka; Frazier, Latoya Ruby; Golden, Thelma; Kaphar, Titus; Leigh, Simone; Marshall, Kerry james; McMillan, Uri; Self, Tschabalala; Shainman, jack; Thoma, Hank Willis; Villalongo, William (New York : Rizzoli Electa Publications, 2017)
Willis Thomas, Hank ; Thomas, Mickalene ; Davis , Noah ; Chanel Abney, Nina ; Mutu, Wangeschi ; Parks, Gordon ; Weems, Carrie Mae ; Ezirku, Awol ; Mnambo , Nandipha ; Hammons, David ; Marshall, Kerry james ; Arrechea , Alexandre ; Diop , Diadji ; Clark, Wesley ; Leigh, Simone ; Simpson, Lorna ; Walker, Kara ; Pendleton, Adam ; Hajjaj, Hassan ; Keïta, Seydou ; Sidibé, Malick ; Shonibare, Yinka ; Ofili, Chris
boek